Genetic engineering and the Third World : an appropriate technology? - Rosset, Peter (2001)
Examines whether genetically engineered crop varieties can raise the productivity of poor Third World farmers, feed the hungry, and reduce poverty. Focuses primarily on agricultural production of food stuffs for domestic consumption.